Readability of Prostate Cancer Information Online: A Cross-Sectional Study. Issue 5 (September 2018) - Basch, Corey H.; Ethan, Danna; MacLean, Sarah A.; Fera, Joseph; Garcia, Phillip; Basch, Charles E.
Reading and understanding health information, both components of health literacy, can influence patient decisions related to disease management. Older adults, the population of males at greatest risk for prostate cancer, may have compromised capacity to understand and use health information. The purpose of this study was to determine the readability of prostate cancer materials on the Internet using five recommended readability tests. Using a cleared Internet browser, a search was conducted for "prostate cancer." The URLs of the first 100 websites in English were recorded to create the sample. The readability scores for each website were determined using an online, recommended service. This service generates five commonly recommended readability tests. All five tests revealed that the majority of websites had difficult readability. There were no significant differences identified between websites with .org, .gov, or .edu extension versus those with .com, .net, or other extension. It is apparent that the Internet is used often as a resource for health-related information. This study demonstrates that the large majority of information available on the Internet about prostate cancer will not be readable for many individuals.